Al Capone shines my shoes - Choldenko, Gennifer, 1957- (Dial Books for Young Readers, 2009)
Moose Flanagan, who lives on Alcatraz along with his family and the families of the other prison guards, is frightened when he discovers that noted gangster Al Capone, a prisoner there, wants a favor in return for the help that he secretly gave Moose.